2018
DOI: 10.1111/bjhp.12294
|View full text |Cite
|
Sign up to set email alerts
|

Parental supervision for their children's toothbrushing: Mediating effects of planning, self‐efficacy, and action control

Abstract: While national recommendations are provided to guide parents in promoting good oral hygiene practices with their children, current results show the importance of going beyond simple knowledge transmission to support parents' intentions to supervise their children's toothbrushing actually materialize. Current findings make a significant contribution to the cumulative empirical evidence regarding self-regulatory components in health behaviour change and can inform intervention development to increase parents' pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 52 publications
4
61
0
Order By: Relevance
“…Future analyses should explore which factors might contribute to these differences. Family conditions and social variables are key candidates for such analyses [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Future analyses should explore which factors might contribute to these differences. Family conditions and social variables are key candidates for such analyses [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…13 Good oral hygiene is the practice of keeping oral cavity, teeth, and gums clean and healthy, in order to prevent disease, 14 and it is important for a person's quality of life and physical and psychological health. 15 Globally, more than 530 milion children suffer from caries of primary teeth. 16 With all the advances in research on the risk factors associated with poor oral health, preventive measures are the essential key factor for good oral hygiene, that is through the removal of dental biofilm (plaque), with toothbrushing as the most common means of an effective dental care at home.…”
mentioning
confidence: 99%
“…16 With all the advances in research on the risk factors associated with poor oral health, preventive measures are the essential key factor for good oral hygiene, that is through the removal of dental biofilm (plaque), with toothbrushing as the most common means of an effective dental care at home. 15,17 For parents, toothbrushing at home is usually linked to other routine events in the morning or evening, such as before breakfast and going to bed. 18 There is an association between sleep habits and increased dental caries incidence.…”
mentioning
confidence: 99%
“…In the volition phase, coping self-efficacy, planning, and action control (such as self-monitoring) are proposed as key self-regulatory factors that are important in ensuring an intended behaviour is initiated, and then maintained once initiated (See Figure 1, Schwarzer, 2008). Several studies have showed the usefulness of the HAPA in explaining oral health behaviour in general (Gholami, Knoll, & Schwarzer, 2015;Hamilton, Bonham, Bishara, Kroon, & Schwarzer, 2017;Hamilton, Cornish, Kirkpatrick, Kroon, & Schwarzer, 2018;Hamilton, Orbell, Bonham, Kroon, & Schwarzer, 2018;Lhakhang et al, 2016;Zhou, Sun, Knoll, Hamilton, & Schwarzer, 2015), and specifically in adolescents (Pakpour et al, 2016;Scheerman et al, 2016;. There is also growing support for the effectiveness of HAPA-based interventions in the context of promoting oral hygiene behaviours (e.g.…”
mentioning
confidence: 99%